The Impact of Role Stress on Employed Women Satisfactions The Role of Self-Efficacy - Fereshteh Mansouri Moayyed; Fatemeh Yavari Gohar (مطالعات مدیریت بهبود و تحول, 2017)
Todays, besides the traditional roles of women they play several roles and sometimes there is conflict among them. The role conflict affect their mental and physical health and leads to dissatisfaction. On the other hand, self-efficacy moderates the effect of role stress on their satisfaction. So this is an applied research which has developed to investigate the effect of role stress on women satisfaction in the public section by considering the moderating role of self-efficacy. The statistical population of this study is composed of employed women that holding governmental jobs in Tehran. Based on the Cochran formula 390 individuals have been considered as the statistical sample. For data collection the standard questionnaires were applied. The validity and reliability of the questionnaires were tested and the required changed were applied. As the results show, the relation between role stress and satisfaction among women is direct and meaningful. About self-efficacy, the result show that this moderating variable plays an important role in this model. It means that whatever the self-efficacy is improved in women the negative impact of role stress on their satisfaction is low. It means that by improving self-efficacy in women, they experience a good fleeing to their life.